Preclinical evaluation of 6-Gingerol in modulating gut microbiota and SCFAs to mitigate Clostridium difficile-associated diarrhea in mice - Ma, Fu-Zhi; Zhu, Lin; Li, Meng; Tang, Ze-Wei; Yu, Xiao-Hong; Zhang, Cong-En; Ma, Zhi-Jie (Frontiers in Chemistry, 2025)
Clostridium difficile associated diarrhea (CDAD) is a growing healthcare concern with limited effective treatments. 6-Gingerol, a major bioactive compound in ginger, exhibits notable antibacterial and anti-inflammatory properties, making it a potential alternative therapy. This study combines in vitro and in vivo approaches to evaluate its efficacy against CDAD. In vitro assays determined the half-maximal inhibitory concentration (IC50) and minimum inhibitory concentration (MIC) of 6-Gingerol against C. difficile, which were 61.99 μM and 173.3 μM, respectively, indicating direct antibacterial activity. In vivo, a mouse model of CDAD was used to assess the therapeutic effects of 6-Gingerol. Outcomes included clinical symptoms, C. difficile load, inflammation, intestinal barrier integrity, gut microbiota composition, and short-chain fatty acids (SCFAs) levels. The results showed that in the CDAD mouse model, high-dose 6-Gingerol significantly alleviated CDAD symptoms, reduced C. difficile load (P < 0.001), improved gut barrier function, and suppressed intestinal inflammation. Although it did not notably increase microbial diversity, 6-Gingerol modulated gut microbiota structure—markedly increasing beneficial bacteria such as Lactobacillus acidophilus (P < 0.01) and Bacteroides thetaiotaomicron, while reducing harmful bacteria including Klebsiella pneumoniae and Proteus mirabilis. Targeted quantification revealed restored levels of key SCFAs, particularly acetate (P < 0.001), butyrate (P < 0.01), and valerate (P < 0.001), which are closely linked to gut health and recovery from CDAD. In summary, 6-Gingerol exerts therapeutic effects against CDAD through direct inhibition of C. difficile, regulation of gut microbiota, restoration of SCFA levels, and protection of the intestinal barrier, highlighting its potential as a novel natural treatment for CDAD.